Effect of microwave radiation on the morphology of tetragonal Cu3SnS4 synthesized by refluxing method - Narongrit Tipcompor (2018)
© 2015 Published by Elsevier Ltd. Tetragonal Cu < inf > 3 < /inf > SnS < inf > 4 < /inf > nanostructures were synthesized in the solution precursors containing CuCl < inf > 2 < /inf > ·2H < inf > 2 < /inf > O, SnCl < inf > 2 < /inf > ·2H < inf > 2 < /inf > O and thiourea (NH < inf > 2 < /inf > CSNH < inf > 2 < /inf > ) in ethylene glycol by conventional refluxing and microwave refluxing methods at an ambient condition. Cu(I) < inf > 2 < /inf > Cu(II)Sn(IV)S < inf > 4 < /inf > of the as-synthesized products were detected by X-ray diffraction (XRD), selected area electron diffraction (SAED) and X-ray photoelectron spectroscopy (XPS). Scanning and transmission electron microscopy (SEM and TEM) revealed the gradual transformation of nanoparticles into curved nanoscales grown out of rods synthesized by conventional refluxing (CR) method, and into flower-like particles synthesized by microwave-assisted refluxing (MR) method. Prominent Raman peaks of CR and MR products were respectively detected at 316 and 318 cm < sup > -1 < /sup > , including photoluminescence (PL) emission at 372 nm and 367 nm due to interband electron-hole recombination. Possible formation mechanism was also proposed according to the experimental results.